From Microcirculation to Aging-Related Diseases: A Focus on Endothelial SIRT1 - Martin Law; Pei-Chun Wang; Zhong-Yan Zhou; Yu Wang (Pharmaceuticals, 2024)
Silent information regulator sirtuin 1 (SIRT1) is an NAD+-dependent deacetylase with potent anti-arterial aging activities. Its protective function in aging-related diseases has been extensively studied. In the microcirculation, SIRT1 plays a crucial role in preventing microcirculatory endothelial senescence by suppressing inflammation and oxidative stress while promoting mitochondrial function and optimizing autophagy. It suppresses hypoxia-inducible factor-1α (HIF-1α)-mediated pathological angiogenesis while promoting healthy, physiological capillarization. As a result, SIRT1 protects against microvascular dysfunction, such as diabetic microangiopathy, while enhancing exercise-induced skeletal muscle capillarization and energy metabolism. In the brain, SIRT1 upregulates tight junction proteins and strengthens their interactions, thus maintaining the integrity of the blood−brain barrier. The present review summarizes recent findings on the regulation of microvascular function by SIRT1, the underlying mechanisms, and various approaches to modulate SIRT1 activity in microcirculation. The importance of SIRT1 as a molecular target in aging-related diseases, such as diabetic retinopathy and stroke, is underscored, along with the need for more clinical evidence to support SIRT1 modulation in the microcirculation.